A survey about gender diversity in a more gender-balanced IT firm - Santos, A. L.; Alexandre, J. D.; Meireles, F. (2021 4th International Conference of the Portuguese Society for Engineering Education (CISPEE), 2021)
We present a case study of Truewind, a mid-size IT consulting company whose distribution of employees is significantly more gender-balanced than the norm. Whereas worldwide employment of women in the ICT sector hardly reaches 20%, women make up almost one third of the developers of the main office of this company. We conducted a case study to gain an understanding of which factors are perceived to contribute to such a gender distribution, and how its employees see it as an advantage. A survey revealed that, independently of gender, employees value gender diversity, pointing out advantages on teamwork, organizational climate, and critical thinking. Further, we collected factors that contribute to the retention of women, which in great part refer to organizational climate and work conditions. Up to a quarter of the IT consultants of Truewind have majored in non-ICT fields, changing their career path mostly from other STEM disciplines.